Simultaneous effect of naringenin and beta-catenin signaling inhibitor C-82 on modulating gene expression and functional pattern of mesenchymal stem cells from endometriosis patients - Hoda Fazaeli; Faezeh Davoodi Asl; Azar Sheikholeslami; Mohsen Sheykhhasan; Naser Kalhor; Leila Naserpour; Rahil Jannatifar; Seyedeh Saeideh Sahraei (Iranian Journal of Basic Medical Sciences)
Objective(s): One of the leading causes of endometriosis is the return of menstrual blood flow into the pelvic cavity and the establishment of menstrual blood mesenchymal stem cells (MenSCs) outside the uterus. MenSCs from endometriosis patients (E-MenSCs) and healthy women have been shown to vary in terms of surface markers and gene expression, which may suggest the involvement of these cells in the development and expansion of ectopic lesions. This study aimed to investigate the effects of beta-catenin signaling inhibitor C-82 and naringenin as PI3K signaling pathway inhibitors on E-MenSCs to modulate their gene expression and functional pattern. Materials and Methods: Briefly, E-MenSCs isolated by density-gradient centrifugation were treated with C-82 and naringenin, and the genes and pathways related to inflammation, proliferation, and survival were evaluated. E-MenSCs showed increased early apoptosis and decreased levels of ROS, IL-6 and IL-8, ER, α-SMA, and Ki-67 protein expression. Results: Our results shed light on the function of C-82 and naringenin in modulating E-MenSCs. Conclusion: However, more research is needed to analyze the precise effects of small molecule C-82 and naringenin on endometriosis.